2012
DOI: 10.1007/s10517-012-1749-x
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization of Hepatocellular Carcinoma Tissue Depends on Its Differentiation Degree

Abstract: Quantitative characteristics of vessels in hepatocellular carcinoma and adjacent liver tissue were studied by morphometric methods after immunohistochemical staining for CD34 and CD105. The number of immunopositive vessels decreased with reduction of tumor histological differentiation degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The above changes confirm the data above about the change of immunophenotype of endothelial cells during hepatocarcinogenesis. According to our previous studies, the degree of HCC vascularization depends on the degree of its histological differentiation: with a decrease in the degree of HCC differentiation, there is a progressive decline in the number of blood vessels [9].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The above changes confirm the data above about the change of immunophenotype of endothelial cells during hepatocarcinogenesis. According to our previous studies, the degree of HCC vascularization depends on the degree of its histological differentiation: with a decrease in the degree of HCC differentiation, there is a progressive decline in the number of blood vessels [9].…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the identification of HCC development, progression, and correction processes associated with angiogenesis is an important task [7,8]. We have previously demonstrated that the morphological characteristics of HCC vascularization depend on the degree o histological differentiation [9].…”
Section: Introductionmentioning
confidence: 99%
“…The angiogenic activity of HCC correlates with the risk of metastasis and prognostic significance [27]. Previous research reported that anti-angiogenesis might be highly efficient for the treatment of HCC by inhibiting angiogenesis in tumor tissues [28e30].…”
Section: Discussionmentioning
confidence: 99%
“…The growth and metastasis of malignant tumors relies on angiogenesis ( 1 , 2 ). When the tumor volume exceeds 2–3 mm 3 , due to the ensuing ischemia and hypoxia, new capillaries are generated to maintain tumor growth ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…An abundance of blood vessels may provide enough nutrients to the tumor tissue and remove various degradation products, and tumor cells can also undergo hematogenous metastasis after they enter the circulation via the blood vessels; otherwise, the tumor may undergo degenerative necrosis ( 5 ). The proliferation, invasion and metastasis of malignant tumors are closely related to tumor-induced angiogenesis ( 1 , 2 ). Neovascularization provides sufficient oxygen and nutrients for the proliferation, infiltration and metastasis of tumor cells ( 2 ).…”
Section: Introductionmentioning
confidence: 99%